Water Demand Forecast in the Baiyangdian Basin with the Extensive and Low-Carbon Economic Modes - T. L. Qin; D. H. Yan; G. Wang; J. Yin (Journal of Applied Mathematics)
The extensive and low-carbon economic modes were constructed on the basis of population, urbanization level, economic growth rate, industrial structure, industrial scale, and ecoenvironmental water requirement. The objective of this paper is to quantitatively analyze effects of these two economic modes on regional water demand. Productive and domestic water demands were both derived by their scale and quota. Ecological water calculation involves the water within stream, wetland, and cities and towns. Total water demand of the research region was obtained based on the above three aspects. The research method was applied in the Baiyangdian basin. Results showed that total water demand with the extensive economic mode would increase by 1.27 billion m3, 1.53 billion m3, and 2.16 billion m3 in 2015, 2020, and 2030, respectively, compared with that with low-carbon mode.